Trends in HPV Testing for Patients With Sinonasal Squamous Cell Carcinoma: A National Analysis. (28th December 2021) - Tseng, Christopher C.; Gao, Jeff; Barinsky, Gregory L.; Fang, Christina H.; Hsueh, Wayne D.; Grube, Jordon G.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objective: The objective of this study was to analyze national trends in human papillomavirus (HPV) testing for patients diagnosed with sinonasal squamous cell carcinoma (SNSCC). Study Design: Retrospective database study. Setting: National Cancer Database (2010‐2016). Methods: Cases from 2010 to 2016 with a primary SNSCC diagnosis and known HPV testing status were extracted from the National Cancer Database. Univariate and multivariate analyses were then performed to assess differences in socioeconomic, hospital, and tumor characteristics between tested and nontested patients. Results: A total of 2308 SNSCC cases were collected, with 1210 (52.4%) HPV tested and 1098 (47.6%) not tested. On univariate analyses, patient age, insurance, income quartile, population density, treatment facility location, and tumor grade were significantly associated with HPV testing status. After multivariate logistic regression modeling, living in a suburban area had lower odds of HPV testing as compared with living in urban areas (odds ratio, 0.74 [95% CI, 0.55‐0.99]; P =. 041), while tumor grade III/IV had higher odds than grade I (odds ratio, 1.73 [95% CI, 1.29‐2.33]; P <. 001). HPV‐tested patients had a similar 5‐year overall survival to nontested patients (48.3% vs 45.3%, log‐rank P =. 405). A sharp increase in HPV testing rates was observed after 2010 ( P <. 001). Conclusion: Among patients with SNSCC, those with high‐grade tumors were more likely to be tested for HPV, while patients with a suburban area of residence were less likely. Additionally, there was no significant survival benefit to HPV testing, with tested and nontested groups having similar overall survival. Level of evidence: 4.